2019
DOI: 10.3390/nu11122898
|View full text |Cite
|
Sign up to set email alerts
|

Poor Oral Health as a Determinant of Malnutrition and Sarcopenia

Abstract: Aging is accompanied by profound changes in many physiological functions, leading to a decreased ability to cope with stressors. Many changes are subtle, but can negatively affect nutrient intake, leading to overt malnutrition. Poor oral health may affect food selection and nutrient intake, leading to malnutrition and, consequently, to frailty and sarcopenia. On the other hand, it has been highlighted that sarcopenia is a whole-body process also affecting muscles dedicated to chewing and swallowing. Hence, mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
169
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 176 publications
(182 citation statements)
references
References 170 publications
(213 reference statements)
2
169
0
11
Order By: Relevance
“…Some of the most useful variables are common wealth, nationality, the belonging to an ethnic group, age and employment. General health status, systemic disease [11], such as metabolic syndromes, syndromic diseases [11][12][13] causing dental abnormalities and immune dysfunction issues can lead to severe complications and poor oral conditions [14]. Within a population, there are significant differences between groups of different ages and employment.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most useful variables are common wealth, nationality, the belonging to an ethnic group, age and employment. General health status, systemic disease [11], such as metabolic syndromes, syndromic diseases [11][12][13] causing dental abnormalities and immune dysfunction issues can lead to severe complications and poor oral conditions [14]. Within a population, there are significant differences between groups of different ages and employment.…”
Section: Introductionmentioning
confidence: 99%
“…In modern dentistry, the use of titanium implants to restore edentulous areas of various extension is a very common practice [1][2][3], followed by a great percentage of long-term success [4]. Systemic or syndromic diseases [5,6] and immune disorders [7] should be evaluated before the implant placement in order to avoid post-operative bleeding-related complications [8,9] and to achieve better outcomes. An accurate exam of the bone crest, in terms of width and height, is also important for proper planning of the implant [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Oral health problems have been reported as common health conditions in older adults and hospitalized patients [17] [18] [27] [28]. Several points are known about the relationship between oral health problems and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that poor oral health is associated with periodontal disease, dental caries, hyposalivation, and tooth loss or edentulousness, which pose risks of chewing di culties, decreased masticatory function, and dysphagia [35] [36]. These oral problems may induce a preference for soft and easily chewable food and a need for changes in food texture to prevent aspiration and choking, leading to poor nutritional intake and undernutrition, and nally to sarcopenia, frailty, and decreased physical function [17] [37] [38].…”
Section: Discussionmentioning
confidence: 99%